2020
DOI: 10.1186/s13058-020-01276-9
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein-mediated regulation of lipid metabolism induces distinctive effects in different types of breast cancer cells

Abstract: Background The highest incidence of breast cancer is in the Western world. Several aspects of the Western lifestyle are known risk factors for breast cancer. In particular, previous studies have shown that cholesterol levels can play an important role in the regulation of tumor progression. Methods In the present study, we modulated cholesterol metabolism in the human breast cancer cell lines MCF-7 and MDA-MB-231 using a genetic approach. Apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
2
13
1
Order By: Relevance
“…Consistent with our ndings, Ben pointed out that especially in breast cancer, APOE can inhibit the proliferation and migration of tumor cells by regulating cholesterol metabolism, and APOE can be used as a target to improve prognosis (29). Moreover, APOE can regulate cancer progression by regulating lipid metabolism via TGFβ, EMT, ER signaling pathways (29,30). Therefore, these results indicated that the function of the APOE gene may be related to cancer and cancer-related pathways, and APOE may mediate the occurrence of PTC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our ndings, Ben pointed out that especially in breast cancer, APOE can inhibit the proliferation and migration of tumor cells by regulating cholesterol metabolism, and APOE can be used as a target to improve prognosis (29). Moreover, APOE can regulate cancer progression by regulating lipid metabolism via TGFβ, EMT, ER signaling pathways (29,30). Therefore, these results indicated that the function of the APOE gene may be related to cancer and cancer-related pathways, and APOE may mediate the occurrence of PTC.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies had shown that elevated cholesterol levels can increase the risk of cancer. Consistent with our ndings, Ben pointed out that especially in breast cancer, APOE can inhibit the proliferation and migration of tumor cells by regulating cholesterol metabolism, and APOE can be used as a target to improve prognosis (29). Moreover, APOE can regulate cancer progression by regulating lipid metabolism via TGFβ, EMT, ER signaling pathways (29,30).…”
Section: Discussionsupporting
confidence: 81%
“… 19 A study by Ben Hassen et al indicated that apoAI could retard the epithelial-to-mesenchymal transition process, which was considered as a key mechanism for chemoradiation resistance of cancer cells. 20 This provided a possible explanation for the negative correlation between serum apoAI level and tumor response to NACRT.…”
Section: Discussionmentioning
confidence: 94%
“…Further research has found that M2 macrophage polarization from GC, involving the JAK2/STAT3 signaling pathway, is attenuated by blockading the secretion of IL-6/IL-8 ( 63 ). Most likely, M2 macrophages modulate lipid metabolism by deriving apolipoprotein E and then remodel the cytoskeleton to support migration in GC ( 64 , 65 ). Especially, M2 macrophage can exacerbate the FA β-oxidation and promote the 5-fluorouracil (5-FU) chemoresistance in GC ( 66 ).…”
Section: Metabolic Alteration In the Gc Immune Microenvironmentmentioning
confidence: 99%